2015
DOI: 10.1260/1369-4332.18.11.1859
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Behavior of Conical Shell Foundations Composed of Reactive Powder Concrete Embedded on Sandy Soil

Abstract: Many forms of shells are available for use as foundations. Then frustum of a cone in the upright position can serve as footing for columns or raft for structure such as chimneys. Reactive Powder Concrete (RPC) is an ultra-high strength, low porosity material with high cement and silica fume contents and steel fibers. RPC uses low water-binder ratios and new generation superplasticizers with eliminating the coarse aggregates, all optimized particle size less than 600 micrometers. RPC can be readily used in a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For the purpose of conducting experiments, a full load-frame assembly was developed and built. Scale models of conical shell foundations set in sand were prepared by Fattah et al [13] using RPC mixed with varying ratios of silica fume. Incorporating steel fibers into RPC footings offers several advantages, including increased stiffness, decreased crack width, and a reduced crack propagation rate.…”
Section: Experimental Overview Researchesmentioning
confidence: 99%
“…For the purpose of conducting experiments, a full load-frame assembly was developed and built. Scale models of conical shell foundations set in sand were prepared by Fattah et al [13] using RPC mixed with varying ratios of silica fume. Incorporating steel fibers into RPC footings offers several advantages, including increased stiffness, decreased crack width, and a reduced crack propagation rate.…”
Section: Experimental Overview Researchesmentioning
confidence: 99%
“…Also, the reduction of bearing capacity has been observed due to the increase in the burial depth of geotextile layers. Furthermore, the investigations indicated that the failure wedge of shell foundations in reinforced backfill conditions is formed deeper than that of conventional flat ones [17,18].…”
Section: Introductionmentioning
confidence: 99%